Assessing Senior High School Students’ Awareness of Sustainable Development Goals in a Philippine STEM School - Jericho Padilla; Jerile Mae Casimiro; Carlo Amigable (Science Education International)
This study examines senior high school students’ awareness and integration of the Sustainable Development Goals (SDGs) within a Philippine STEM school context. Employing a quantitative descriptive design, the research used a structured survey to assess students’ self-reported SDG knowledge, information sources, subject penetration, and the impacts on personal lives and career planning, culminating in the development of an Education for Sustainable Development (ESD) model. Findings reveal that formal education is the predominant source of SDG awareness, yet students show limited understanding of the SDGs’ temporal and geographic scopes. While subjects such as STEM Research, Social Science, Science Elective, and Science Core exhibit robust SDG integration, disciplines like Mathematics demonstrate significant gaps. Furthermore, path analysis indicates that both self-reported knowledge and information channels play a crucial role in shaping learning outcomes, personal engagement, and future career choices – results that underpin the development of a comprehensive Education for Sustainable Development model. These outcomes advocate for the adoption of innovative, cross-curricular pedagogical strategies, and enhanced career guidance programs to more effectively align sustainability education with national strategic frameworks and prepare students for sustainability-driven professional pathways.